Analisis Kemampuan Pemecahan Masalah Matematika Materi Aritmetika Sosial Ditinjau Dari Gaya Belajar Siswa - Hijriani, Laelatul; Sri Subarinah; Syahrul Azmi; Baidowi (FKIP Universitas Mataram, 2024)
The purpose of this study was to describe students' problem solving abilities in social arithmetic material in terms of learning style. It was a qualitative descriptive study. The instruments for this research are questionnaires, tests and interviews. Of the 151 students given a learning style questionnaire, there were 100 students with a visual learning style, 30 auditory students, and 21 kinesthetic students. A total of 32 students were given a test, then 9 subjects were selected to be interviewed consisting of 3 students from each learning style and selected through purposive sampling to deepen the data. Qualitative data analysis uses 3 stages, namely reduction, presentation and drawing conclusions. The research results show that students with a visual learning style are able to reach the stage of understanding problems, making plans, solving problems and checking again. Visual students fall into the category of high problem solving abilities. Auditory students are able to reach the stage of understanding problems, making plans, solving problems. Auditory students fall into the category of moderate problem solving abilities. Kinesthetic students are able to reach the stage of understanding problems and making plans. Kinesthetic students fall into the category of low problem solving abilities.